Transactions Between Child Social Wariness and Observed Structured Parenting: Evidence From a Prospective Adoption Study. Issue 5 (28th February 2013) - Natsuaki, Misaki N.; Leve, Leslie D.; Harold, Gordon T.; Neiderhiser, Jenae M.; Shaw, Daniel S.; Ganiban, Jody; Scaramella, Laura V.; Reiss, David
Abstract : This investigation examined the mutual influences between structured parenting and child social wariness during toddlerhood using a longitudinal adoption design. The sample consisted of 361 adoption‐linked families, each including an adopted child, adoptive parents, and a birth mother. Heightened social wariness in children at age 18 months predicted reduced levels of observed structured parenting (i.e., less directive parenting with fewer commands and requests) in adoptive mothers at age 27 months. Adoptive fathers' lower structured parenting at age 18 months predicted subsequent elevation in child social wariness. Birth mothers' history of fear‐related anxiety disorders was not associated with child social wariness. Findings highlight the role of dynamic family transactions in the development of social wariness during toddlerhood.